Gemini AI as a Writing Catalyst: Boosting Fluency, Coherence, and Confidence in EFL Composition - Hasanah, Evi; Nurul Azizah, Siti; Febtwenesty, Febtwenesty (Journal of English Education, 2025)
Google now has its own AI, Gemini AI, which can be used in various sectors of the learning education, industry, medicine, science and can still be explored more. In this study investigates how Gemini AI will impact on students' learning of writing skills, effectiveness, advantages and disadvantages in language learning. The researchers used the quasi-experimental method for 60 students from the eleventh grade in senior high school 10 Palembang. The result of this study indicate that the use of Gemini AI can serve as an effective tool in improving students' writing skills, provided that its use is done judiciously and under the supervision of teachers. It is important to maintain a balance between the utilization of technology and the development of students' natural abilities. Teachers have a crucial role in guiding students not only to rely on AI, but also to develop their creativity and writing skills independently. We can concluded that the use of Gemini AI has a significant impact on the writing skills of eleventh grade students at SMAN 10 Palembang. Students who engaged in learning with the help of Gemini AI showed more significant improvement in writing skills compared to students who were not taught using Gemini AI. This improvement was seen in various aspects, including writing structure, language grammar, coherence, and vocabulary selection.